2011
DOI: 10.14295/rbho.v17i2.706
|View full text |Cite
|
Sign up to set email alerts
|

Produção de mudas de Zínia elegans em substratos à base de resíduos agroindustriais e agropecuários em diferentes tamanhos de recipientes

Abstract: Produção de mudas de Zínia elegans em substratos à base de resíduos agroindustriais e agropecuários em diferentes tamanhos de recipientes(1,2) RESUMOO substrato e o tamanho do recipiente são fatores importantes para a obtenção de mudas de qualidade. Os objetivos desse trabalho foram testar oito substratos e três tipos de recipientes na produção de mudas de zínia. Os substratos foram formulados com os seguintes compostos: bagaço de cana e esterco bovino (composto 1); lixo de frutas e de verduras mais esterco bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 0 publications
0
8
0
4
Order By: Relevance
“…Mendonça et al (2003) argue that containers with a higher volume provide a better growth of the root system of seedlings. Sousa et al (2011) found that the use of trays with 126 cells was more efficient when compared with trays with 150 and 228 cells for the production of Zinnia spp. seedlings.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Mendonça et al (2003) argue that containers with a higher volume provide a better growth of the root system of seedlings. Sousa et al (2011) found that the use of trays with 126 cells was more efficient when compared with trays with 150 and 228 cells for the production of Zinnia spp. seedlings.…”
Section: Resultsmentioning
confidence: 99%
“…In the production of Zinnia elegans seedlings in trays with 126 cells, there was an increased seedling development, with a greater height, shoot dry matter and percentage of survival (Sousa et al, 2011). In addition, the container size used in seedling production directly affects the final cost.…”
Section: Introductionmentioning
confidence: 99%
“…The highest percentage of emergence 51.5 and 55% of seeds in substrates containing SM + SS and SM + SS + SA can be attributed to favorable conditions to germination, such as the availability of water and oxygen in quantities and ideal proportions. According to Souza et al (2011), there are some factors that interfere in the germination process of seeds in different substrates such as light, oxygen, temperature and water, beside of conditions inherent to the seed as numbness. Another considerable factor on the germination capacity is the genotypic inheritance.…”
Section: Resultsmentioning
confidence: 99%
“…It presents flowers of the type daisy simple, folded or frizzy, often used in parks and gardens of tropical and subtropical regions. It is an ornamental plant also cultivated for the production of cut flowers (Szopińska and Politycka, 2016) because of their long-term durability, being suitable, also, for the lawn hedge row and massive in full sun in regions of mild and tropical temperatures (Souza et al, 2011). Since a few years ago, the system for produce seedlings is getting modern and advanced on their technological level, because of the adaptation of new techniques, like protected cultivation, intermittent nebulization, climate control in the greenhouses and the use of modern inputs, such as re-usable containers, sterile and biodegradable substrates.…”
Section: Introductionmentioning
confidence: 99%
“…O resíduo da bagana de carnaúba é abundante nas regiões de ocorrência dessa palmeira e utilizado com sucesso nas diversas etapas do desenvolvimento das mudas, desde a germinação até o estabelecimento em campo. No entanto, tem ocupado lugar de destaque na composição de substratos, sendo recomendado por diversos autores (SOUSA et al, 2012;ALBANO et al, 2017;SILVA et al, 2017).…”
Section: Metodologiaunclassified